Evaluation of Post-operative Pain after Irrigation Using End-vented NaviTip Tips versus Vibringe Sonic Irrigating System in Teeth with Acute Pulpitis with Apical Periodontitis: A Randomized Clinical Trial - Mohamed Ali, Mohamed Elsaeed; Magdy, A.; Hussien, W. (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: This clinical study was conducted to evaluate and compare the post-operative pain after the using of two different irrigating techniques: Vibringe sonic irrigating system with end-vented NaviTip and conventional needle with end-vented NaviTip immediate postoperatively and 4, 12, 24, 48, and 72 h and 7 days utilizing a numerical rating scale (NRS). METHODS: Thirty-eight patients with acute pulpitis with apical periodontitis were involved in this study. Root canals were prepared using NiTi ProTaper Universal rotary system then randomized into two equal groups according to the technique used for irrigation Group A, Vibringe sonic irrigating system with end-vented NaviTip and Group B, conventional syringe with end-vented NaviTip® irrigating tip. The needles of irrigation were penetrated 2 mm shorter than the working length. The trial design of this study is a parallel randomized controlled trial. RESULTS: All demographic data, clinical and radiographic findings, and modified NRS scores obtained from patients were statistically analyzed. Results showed that there was no statistically difference between the two groups regarding the demographic data, prevalence of pre-operative pain, after 4 h, 12 h, 24 h, and 48 h and 7 days, while in both groups, there was a statistically significant decrease in pain intensity preoperatively compared with all other time periods. CONCLUSION: There is no statistical significance difference between Vibringe sonic irrigating syringe with endvented needle and conventional syringe with end-vented NaviTip, while in both groups, there was a statistically significant decrease in pain intensity preoperatively compared with all other time periods.